Analisis Faktor Faktor yang Melatar Belakangi Kenakalan Santri di Pondok Pesantren - Zaid Al Qodli, Achmad; Haryanto, Budi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2024)
In Indonesia, pesantren are well known as religious teaching centers that play an important role in promoting Islamic principles. In reality, pesantren face the problem of santri delinquency even though they are considered educational institutions that emphasize religious standards. This study seeks to understand the background and underlying factors of santri delinquency in pesantren schools, investigate the influence of moral education on santri behavior, and assess aspects of parenting that contribute to delinquency. Interviews with teachers, pesantren management, and informants of students who have been in trouble were conducted using qualitative methodology. The results of this study are expected to provide deep insights that will help in the development of policies and preventive measures aimed at raising a new generation of morally and ethically conscious students.